Pyramid capitalism: Cronyism, regulation, and firm productivity in Egypt - Ishac Diwan; Philip Keefer; Marc Schiffbauer (Inter-American Development Bank (IDB), 2016)
Using a large, original database of 385 politically connected firms under the Mubarak regime in Egypt, we document for the first time the negative impact of cronyism on economic growth. In the early 2000s, a policy shift in Egypt led to the expansion of crony activities into new, previously unconnected sectors. 4-digit sectors that experienced crony entry between 1996 and 2006 experienced lower aggregate employment growth during the period than those that did not. A wide array of supporting evidence indicates that this effect was causal, reflecting the mechanisms described in Aghion et al. (2001), and not due to selection. Crony entry skewed the distribution of employment toward smaller, less productive firms; crony firms did not enter into sectors that would have also grown more slowly even in the absence of crony entry; and they enjoyed multiple regulatory and fiscal privileges that reduced competition and investments by non-crony firms, including trade protection, energy subsidies, access to land, and favorable regulatory enforcement. Moreover, energy subsidies and trade protection account for the higher profits of politically connected firms.
Keywords: D72; D24; O47; 330; cronyism; growth; political connections; productivity; regulation